Depression and Anxiety among Iraqi Women: A Systematic Review - Kathryn Mishkin; Bibi Chaterpateah; Valerie Bresier; Jaleen Fraser (Hawler Medical University, 2018)
Background and objective: Maternal mental health is considered an important subject among leading public health experts. Women are two to three times more likely to be diagnosed with mental illness compared to men. According to the World Health Organization, depression will be the biggest contributor to burden of disease among women by 2020. Chronic stress, experiencing war, and history of abuse are associated with mental illness. Iraq has experienced years of challenging circumstances due to the political and social environment as well as physical barriers to health care services. This paper presents findings from literature about mental illness among Iraqi women. Methods: A comprehensive literature review was conducted using PubMed, Google Scholar, and EBSCO Academic Search Complete to identify studies focused on mental illness in Iraq. Search terms included: maternal, anxiety, depression, Iraq, Middle Eastern and North African region, and women. Cross-sectional, cohort, and case-control studies were included. Results: Five papers were found that focused exclusively on mental illness in Iraq. Two described maternal mental illness and three focused on mental illness in the general population, with two of the three including information specific to women. Results suggest that the rate of mental illness among Iraqi women is not different from women in other countries. However, because there is a difference of seven years between the Iraqifocused study and other global studies, additional new research is required to best compare rates. Interestingly, Iraqi women experience maternal mental illness at higher rates than other women. While the global average rate for mental illness in pregnancy or the postpartum period is estimated at 15-20%, 37.5% of Iraqi women experience anxiety and 28.5% experience depression. Conclusion: Additional study focusing on women's health and maternal mental health is necessary to describe women at highest risk for mental illness and to inform strategies.